The CM carbonaceous chondrite regolith Diepenveen. (13th May 2019) - Langbroek, Marco; Jenniskens, Peter; Kriegsman, Leo M.; Nieuwenhuis, Henk; De Kort, Niek; Kuiper, Jacob; Van Westrenen, Wim; Zolensky, Michael E.; Ziegler, Karen; Yin, Qing‐Zhu; Sanborn, Matthew E.; Wimpenny, Josh; et al.
Abstract: A carbonaceous chondrite was recovered immediately after the fall near the village of Diepenveen in the Netherlands on October 27, 1873, but came to light only in 2012. Analysis of sodium and poly‐aromatic hydrocarbon content suggests little contamination from handling. Diepenveen is a regolith breccia with an overall petrology consistent with a CM classification. Unlike most other CM chondrites, the bulk oxygen isotopes are extremely 16 O rich, apparently dominated by the signature of anhydrous minerals, distributed on a steep slope pointing to the domain of intrinsic CM water. A small subset plots closer to the normal CM regime, on a parallel line 2 ‰ lower in δ 17 O. Different lithologies in Diepenveen experienced varying levels of aqueous alteration processing, being less aqueously altered at places rather than more heated. The presence of an agglutinate grain and the properties of methanol‐soluble organic compounds point to active impact processing of some of the clasts. Diepenveen belongs to a CM clan with 5 Ma CRE age, longer than most other CM chondrites, and has a relatively young K‐Ar resetting age of 1.5 Ga. As a CM chondrite, Diepenveen may be representative of samples soon to be returned from the surface of asteroid (162173) Ryugu by the Hayabusa2 spacecraft.